KOMPONEN FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN RUMPUT LAUT EUCHEUMA COTTONII DI PERAIRAN DESA PAJUKUKANG BANTAENG - Saadatul Husna; Nurlaida Nurlaida; Yusriadi Yusriadi; Hermin Utami; najmah najmah (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2023)
Red seaweed (Eucheuma cottoni) is a plant that has high cultivation potential and is growing rapidly. Bantaeng Regency is one of the 15 seaweed processing centers in Indonesia. The use of seaweed is very diverse, both for food, feed, fertilizer, cosmetics and pharmaceuticals. This is related to the content of nutrients, minerals and bioactive compounds contained in seaweed. This research aims to determine the water content, ash content, phytochemical compound and antioxidant activity of red seaweed in the waters of Pajukukang Village Bantaeng. The research result showed that water content and ash content of red seaweed were 7.21%,17.626% respectively. Red seaweed ethanol extract contains alkaloids, flavonoids, saponins, and steroids. The result of antioxidant test showed that the red seaweed ethanol extract has weak antioxidant activity with IC50 value of 961,83 ppm.